Audit Committee, Financial Condition, and Firm Performance: Empirical Evidence From Indonesia - Ekawati Jati Wibawaningsih; Lidya Primta Surbakti (DINASTI RESEARCH, 2020)
This study has examined the characteristics of the audit committee (size, independence, and expertise) in addition to financial Condition (leverage and firm size) in increasing firm performance. The random effect with panel data regression was applied on 309 firm-year observations of the manufacturing companies listed in the Indonesian Stock Exchange (IDX) for the period of 2016 - 2018. Return on Assets was used as the measurement of firm performance. This study’s results show a significant and positive relationship between firm size with performance and a significant negative relationship between leverage and firm performance. However, the findings show no significant relationship between the characteristics of the audit committee and firm performance. The results of this study have implications for investors, regulators, and market participants. Policy makers might use these findings, especially regarding the characteristics of the audit committee and financial conditions, for improving the performance of the companies in Indonesia